Obesity in pregnant adolescents: clinical correlates, maternal and fetal outcomes - Alfama, Cecília Ogando (2020)
Objective: To evaluate the relationship between pregestational obesity and maternal and fetal outcomes in pregnant adolescents. Methods: Cross-sectional study conducted among puerperal teenagers of a university hospital in Southern Brazil. Structured questionnaires on sociodemographic and obstetric data were applied. Results: We evaluated 500 puerperal adolescents with a mean age of 17.77 ± 1.36. Of these, 31.2% (n=156) had pregestational weight excess. Pregestational weight excess was significantly associated with gestational hypertension (p=0.037) and diabetes (p=0.045), cesarean delivery (p=0.040), and lower adherence to prenatal care (24.7%, p=0.007). Mothers with pregestational weight excess also gained more weight than recommended during pregnancy and had babies with a higher weight (p=0.02) and length (p=0.018). Conclusion: Pregestational weight excess in adolescence is related to unfavorable maternal and fetal outcomes. We emphasize the importance of a closer look at this population still in development to identify nutritional disbalances and promote adequate weight gain.